Understanding multi-stage diffusion process in presence of attrition of potential market and related pricing policy - Singhal, Shakshi; Anand, Adarsh; Singh, Ompal (Yugoslav Journal of Operations Research, 2019)
In this paper, a mathematical model using a three-stage structure is developed to describe the diffusion process of high-technology products. This article investigates the significance of the informed and disinterested potential adopters on the growth pattern of innovation. The suitability of the proposed methodology for real-life scenarios is validated by fitting the model to the actual sales and price data sets from the electronics and semiconductor industries. The present study also incorporates the influence of dynamic price on the decision of the adoption of new products. An optimization problem is also formulated as an optimal control problem with the objective of profit maximization to determine the optimal price of the new technology.